PENGARUH MEDIA SLIDE PRESENTASI DALAM MENUNJANG PENINGKATAN PENGETAHUAN TENTANG GERAKAN SHODAQOH SAMPAH MUHAMMADIYAH PADA SISWA KELAS V SD MUHAMMADIYAH 4 SAMARINDA KALIMANTAN TIMUR - Muhammad Habibi; Rusdi Rusdi (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2018)
Abstract School is one of the means for landfill. Therefore, it needs to be overcome wisely. One way to overcome this is to do rubbish shodaqoh. The movement of rubbish shodaqoh is a program from the Muhammadiyah Environmental Assembly in managing the rubbish to save the environment and make it economical by providing a theological touch in it. The movement of rubbish shodaqoh needs to be understood by students through briefing by using interesting media so that the students can easily understand it. Media was used is presentation slides. The research aim was to know the influence of the presentation slide media in supporting the increase of knowledge about the movement of Muhammadiyah’s rubbish shodaqoh for grade 5 students of Muhammadiyah 4 Elementary School of Samarinda, East Borneo. The type of the research is pre-experiment using one group pretest-postest design. Samples were grade 5 students of Muhammadiyah 4 Elementary School of Samarinda. The sampling technique is carried out by using simple random sampling. The research findings, with the use of the wicoxon test, obtain p-value of 0.000 (< 0.05), so it was concluded that presentation slide media have effect in supporting the increase of knowledge about the movement of Muhammadiyah’s rubbish shodaqoh for grade 5 students of Muhammadiyah 4 Elementary School of Samarinda, East Borneo.